Effect of matrix metalloproteinase 8 inhibitor on resin–dentin bonds. Issue 5 (May 2018) - Ou, Qianmin; Hu, Ya; Yao, Siqi; Wang, Yan; Lin, Xuefeng
Highlights: The activity of MMP-8 in dentin was enhanced by adhesive procedures, while was inhibited by the treatment of MMP-8 inhibitor I (MMP8-I). MMP8-I-treated dentin had significantly higher bond strength and exhibited structural integrity of the collagen network in the hybrid layer. Less nanoleakage was detected in MMP8-I group after 1 day, 6 months and 1 year of storage. Abstract: Objectives: This study investigated the effect of matrix metalloproteinase 8 (MMP-8) on resin–dentin bonds, assessed the mechanical properties of the interfaces over time, and discussed the potential application of MMP-8 inhibitor I (MMP8-I) as a specific MMP-8 inhibitor to be incorporated into dental adhesives. Methods: The activation and inhibition of MMP-8 was detected by colorimetric assay. After 1 day, 6 months and 1 year of storage of Control, MMP8-I, and chlorhexidine (CHX) groups, the microtensile bond strengths (μTBS) were used to evaluate the bond strength and failure mode distributions, and nanoleakage analysis was used to evaluate the minor scattered silver particles. Results: Colorimetric assay showed that the activated MMP-8 was enhanced by adhesive procedures, while it was inhibited by the additional treatment of MMP8-I or CHX. Compared with the Control and CHX groups, the MMP8-I group had significantly higher bond strength and the hybrid layer from the MMP8-I-treated dentin exhibited structural integrity of the collagen network and decreased silver nitrate penetration after 1 year of storage. Significance: MMP-8 inhibition I protects against the degradation of resin–dentin bonds over time, which is better than broad-scale enzyme inhibitor CHX. It shows that MMP8-I may be used in dentistry for preventing collagen degradation within hybrid layers to extend the longevity of resin–dentin bonds.